Accelerating the adoption of Climate-Smart Agriculture (CSA) and Climate Information Services (CIS) Course Modules in African higher education systems: The case of UFHB - Sorho, Fatogoma; Agyare, Wilson Agyei; Amponsah, William; Lamptey, Benjamin; Cherif, Mamadou; Kone, Daouda (2025)
Curricula that prepare youth to use and mainstream CSA/CIS to address the impact of the changing climate in Africa is critically needed. Through AICCRA support, a new Master program was developed and composed of 21 courses, including nine of the 11 course modules developed through AICCRA. The master program is under review by the UFHB board before formal approval. The program will serve as a model for other West African universities looking to integrate CSA and CIS into climate change education.